Ethics and the consumer [videorecording] - Breitenmoser, Kurt; Ferla, Catherine; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2010)
'Shopping, it's a pastime many of us know well. In fact for many people shopping is the ultimate leisure activity. Everyone loves a bargain, but how often do we think of the origins of the products we buy? Who made these products, under what conditions and at what cost to the environment? It may seem like we are getting a cheap deal, but what does the item's production really cost our world? In this Australian-made, curriculum fit program we tackle the issue of ethical consumerism, focusing on the global consumer, ethics, sustaining our future, fair trade and consumer choice'--Container.
Executive producer, Simon GArner
Voice over : Clare Chihambawke
DVD format
Subtitle available in English
Keywords: Consumer behavior; Consumption (Economics) -- Moral and ethical aspects; Consumer education; Consumers